Study of Frequency Selective Surfaces on Radar Cross Section Reduction - Ismail, M.Y.; Shamsani, N. A. N. M. (International Journal of Integrated Engineering, 2009)
With recent technology in radar cross section reduction (RCSR), a periodic array of frequency selective surfaces (FSSs) which exploits a non-metallic ground plane and slot embedded in the patch elements have been presented. In this study, the single layer FSSs with different incidence angles and substrate thicknesses have been investigated and simulated at the X-band frequency range using CST computer model. Based on the FSSs design, the minimum reflection response is shown to be -74.68 dB while the minimum RCS is -5577 dBm2 occurred at the incidence angle which is equal to 75 degree. Moreover, the maximum value of RCS at -4417 dBm2 has been observed when the incident wave and observer is located at the 0 degree which is offers maximum RCS reduction. Analysis of the CST computer model has been integrated with MATLAB 7 to show the reliability of the two computer model in order to study the feasibility of reflection response in reducing RCS. RCS calculations have been carried out using MATLAB 7 computer model in order to investigate the performance of minimum reflection response which offers reduction in RCS. From the simulated results, it can be concluded that, 75 degree’s incidence angles offered the best performance on RCS reduction due to the angles of incidence, minimum reflection response and lower surface current distribution.